MRNAs are sorted for export or degradation before passing through nuclear speckles. Issue 16 (19th July 2018) - Fan, Jing; Kuai, Bin; Wang, Ke; Wang, Lantian; Wang, Yimin; Wu, Xudong; Chi, Binkai; Li, Guohui; Cheng, Hong
Abstract: A significant fraction of mRNAs are degraded by the nuclear exosome in normal cells. Here, we studied where and when these exosome target mRNAs are sorted away from properly exported ones in the cells. We show that upon exosome inactivation, polyA RNAs are apparently accumulated in nuclear foci that are distinct from nuclear speckles (NSs), and provide several lines of evidence supporting that these polyA RNAs mainly correspond to accumulating exosome target mRNAs. These results suggest that exosomal mRNA degradation mostly occurs outside of NSs. In support of this possibility, targeting exosome target mRNAs to NSs stabilizes them by preventing exosomal degradation. Furthermore, inhibiting mRNA release from NSs does not attenuate exosomal degradation in normal cells, and results in polyA RNA accumulation both inside and outside of NSs in exosome inactivated cells, suggesting that passage through NSs is not required for sorting mRNAs for degradation or export. Indeed, exosome target mRNAs that normally do not enter NSs are exported upon exosome inactivation. Together, our data suggest that exosome target mRNAs are mainly degraded in the nucleoplasm before entering NSs and rapid removal of these mRNAs is important for preventing their nuclear export.